The m5C orchestrator NSUN7 drives SPARC/HMGB1 axis–mediated inflammation to exacerbate kidney injury - Yu-hang Dong; Shuai-shuai Xie; Shuai Sun; Yu Ren; Qin Yang; Jie Wei; Rui Hou; Xiang-Yu Li; Jing-wen Wu; Wen-xian Ma; Ju-tao Yu; Meng-ting He; et al. (Proceedings of the National Academy of Sciences, 2026)
Growing evidence indicates that kidney inflammation is a major contributor to the pathogenesis of various renal diseases, including acute kidney injury (AKI). Although RNA modifications have been implicated in regulating kidney inflammation, their precise roles remain largely unknown. Here, we show that kidney inflammation and injury were associated with elevated RNA 5-methylcytosine (m5C) modifications, primarily driven by the NOP2/Sun RNA methyltransferase family member 7 (NSUN7). Both global and kidney-specific deletion of Nsun7 in mice reduced m5C abundance, attenuated inflammatory responses, and decreased macrophage infiltration, underscoring its proinflammatory role in the kidney. Mechanistically, we identified secreted protein acidic and cysteine-rich (SPARC) as a major downstream effector of NSUN7. SPARC upregulation amplified inflammatory responses in renal tubular epithelial cells by interacting with high mobility group box 1 and further promoted proinflammatory macrophage infiltration via tubular-macrophage crosstalk. Notably, therapeutic silencing of Nsun7 using a kidney-specific DNA tetrahedral molecular carrier developed for this study effectively alleviated inflammation and improved renal outcomes in AKI models. Collectively, our findings identify NSUN7 as a key driver of renal inflammation via SPARC regulation and underscore its potential as a therapeutic target in inflammatory kidney diseases.